One teacher one book literacy program in elementary schools - Rosita Husna; Anatri Desstya (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
Literacy is very important for learners and affects their success in terms of learning and living.  The purpose of this study is to explore the implementation, obstacles, and solutions in the implementation of the one-teacher-one-book literacy program at SD Negeri 1 Kuripan, Grobogan.  This research uses a qualitative approach with a case study research design. The data collection techniques used are interviews and documentation. Data analysis techniques are carried out with three procedures, namely data reduction, data presentation, and drawing conclusions. The results of the data analysis show that the implementation of the one-teacher-one-book literacy movement program in elementary schools is carried out by principals, teachers, and students with the main target being teachers. The implementation of the one-teacher-one-book literacy movement program in Grobogan District in 2020 was carried out by participating in a one-teacher-one-book movement training at the Kriyad Grand Master Hotel for 2 days which has been held by the local education office in collaboration with the Grobogan Writers Teachers Association (AGPG) and Media Teachers. Teachers can work on their work in between each teacher's free time. Teachers can print their own work into one book or combine their work with other teachers and then make it into one book. The obstacles encountered in the implementation of the literacy movement program for one-book teachers in elementary schools include constraints on the availability of funds and also time. The establishment of a literacy community is a solution to overcoming the obstacles that occur in the implementation of literacy programs to help teachers' self-development through activities with the community, such as joint book reviews, joint discussions, and exchange of information